Error analysis of Syntactical errors and style errors in scientific articles submitted for publication in Iraqi biological journals (Journal of the College of Basic Education, 2022)
Most of the Iraqi researchers in the biology field write their scientific articles in English although it is not their native language. Linguistic errors can be expected in these articles particularly in verbs, tenses, conjunctions, adverbs, adjective, punctuation marks, spelling, pronouns, and plurals. Hence this study investigates linguistic errors in scientific articles written by those researchers, and published in Iraqi biological journals. The main aim of this study is to promote the level of their scientific writing in linguistic aspects and the linguistic difficulties they face in this genre of writing. The linguistic errors were identified and analyzed in 24 scientific articles from two issues of Iraqi journal of cancer and medical genetics. These scientific articles are not linguistically reviewed. This study focuses on certain syntactical errors and other errors involved punctuation ,capitalization, spelling of writing The results show that errors are committed including verbs forms ,tenses ,active and passive, adverb and adjective, conjunction, auxiliaries, down to spelling punctuation and capitalization, articles , preposition, pronouns, and finally the misuse of plural. Although there are variations between these ,on basis of, of analyzing result data that there are errors committed in these scientific articles.all samples have errors. Some errors are recurrent in forms of tenses, passive voice, and active, adverb, adjective, spelling, punctuation, etc. A big observation was recorded that some researchers strongly need to improve their English level when they write their articles.